Efficacy of prestressed SMA diagonal loops in seismic retrofitting of non-seismically detailed RC beam-column joints. (15th October 2021) - Suhail, R.; Amato, G.; Broderick, B.; Grimes, M; McCrum, D.
Highlights: Active confinement can increase the ultimate strength of BCJ by 20 — 30%. Energy dissipation capacity by 60 — 70%. And, reduce joint shear strain by over 300%. Max. benefit of active confinement was achieved in 50-100 kNs prestress range. Abstract: In this study, a detailed experimental and numerical investigation is carried out to study the efficacy of prestressed SMA diagonal compression loops in seismic retrofitting of non-seismically detailed RC beam-column joints. Prestressed diagonal compression loops exert active confinement to the joint core which is found to perform better than the conventional passive confinement in terms of improving the shear strength, ductility, and energy dissipation capacity. In this study, active confinement of the joint core is achieved by applying in-plane diagonal compression forces using externally fastened prestressed NiTiNb shape memory alloy (SMA) diagonal loops. In the experimental part, two different techniques are investigated to prestress the SMA loops, which are: 1) rapid heat-activated prestressing technique utilizing the shape memory feature of SMAs; and 2) conventional prestressing of SMA loops by mechanical means. In the finite element analysis, a wide range of prestress values (post-tension force) is studied, keeping the basic arrangement same. The efficacy of the retrofitting technique is evaluated in terms of enhancement in strength, ductility, energy dissipation capacity, damage reduction in the specimens, and the ease of application. The results from this study suggest that depending on the applied confinement level, the retrofitting scheme can increase the ultimate strength in the range of 20–30% and the energy dissipation capacity in the range of 60–70% however, no significant enhancement in ductility of the retrofitted specimen may be achieved using this approach. The study also highlights the complexity involved in controlling the material behaviour of NiTiNb SMA wires and the risks associated with the application of SMAs in practical problems.